Marine Microalgae as Indicators of Heavy Metal Pollution in Coastal Ecosystems - Wiya Elsa Fitri; Adewirli Putra; Syamsuardi Syamsuardi; Nofrita Nofrita; Deswati Deswati (Jurnal Kesehatan Medika Saintika, 2025)
Heavy-metal contamination remains a critical ecological threat in tropical coastal ecosystems, particularly along the West Coast of Sumatra, where concentrations of Pb, Cd, and Cu frequently approach or exceed biological stress thresholds. This article evaluates marine microalgae as indicators of heavy metal pollution, combining global biomarker evidence with region-specific hydrodynamic conditions, referring referring to publications from the last six years. The findings reveal strong cross-study convergence in microalgal responses, including chlorophyll degradation, photosynthetic inhibition, oxidative stress, and antioxidant enzyme activation. These biomarker patterns align closely with local observations from Sumatra, indicating that microalgae operate within exposure ranges known to induce sublethal physiological impairment. Hydrodynamic modulation driven by monsoon cycles further amplifies metal bioavailability, producing alternating acute and chronic stress regimes that chemical monitoring alone often fails to detect. This review provides the first integrated assessment linking microalgal biomarker evidence with monsoon-regulated metal dynamics in Indonesian coastal waters. By synthesizing mechanistic, ecological, and environmental data, the study establishes a robust scientific foundation for adopting microalgae as a core component of early-warning systems and coastal biomonitoring frameworks. The findings also highlight methodological gaps and propose future directions to strengthen monitoring programs within a One Health perspective